Review on Effect of various feed additives on Pig production performance - Kumar, Lalit; Vikas; Devi, Dr Asem Ameeta; Khadse, Phalguni N.; Zuyie, Dr. Razouneinuo; Palriya, Paramveer; Sangtam, Tsarila Z.T.; Sanjay (International Journal of Environment, Agriculture and Biotechnology, 2024)
This review provides an exhaustive examination of the efficacy and mechanisms of action of various feed additives in pig diets, including acidifiers, essential oils, prebiotics, probiotics, and feed enzymes. The additives' impact on growth performance, gut health, and antibiotic reduction is critically evaluated. The review elucidates the additives' mechanisms of action, encompassing antimicrobial activity, immune modulation, and nutrient digestion enhancement. A meta-analysis of the additives' effects on growth performance metrics, including average daily gain and gain-to-feed ratio, is presented. The review highlights the necessity for further research to optimize additive usage and elucidate their effects on pig production. Additionally, the importance of tailoring diets to meet the specific needs of young pigs and promoting gut health and development is emphasized. This comprehensive review synthesizes the current state of knowledge on feed additives in pig diets, providing valuable insights for researchers, producers, and industry stakeholders.